Collaboration Between Local Government and Educational Institutions in Developing Educational Innovation Through The Sabernova Program in Sampang Regency - Iman Teguh Susanto; Ika Devy Pramudiana; Nihayatus Sholichah (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
Educational innovation in the era of regional autonomy requires collaboration between local governments and educational institutions to create quality and adaptive educational services. Sampang Regency, through the SABERNOVA Program, strives to foster a culture of local innovation in education by collaboratively involving various educational actors. However, the implementation of collaboration in developing educational innovation still faces various obstacles, such as variations in school capacity, a lack of human resources, and an unbalanced culture of innovation in the education sector. This study focuses on analyzing collaboration between local governments and educational institutions, the implementation of educational innovation, and the factors that support and hinder the implementation of the SABERNOVA Program in Sampang Regency. This research applies a qualitative approach through case studies. Data collection was conducted through observation, in-depth interviews, and documentation involving the Education Office, Regional Development Planning, Research and Development Agency of Sampang Regency, school principals, and teachers as informants in the research. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The research findings indicate that collaboration is realized through coordination, support, communication involving participation, and providing space for schools to innovate in education. The implementation of SABERNOVA encourages innovation in learning, digitalization of school administration, and strengthening the culture of innovation in the education sector. Key supporting factors include local government commitment and school participation, while key barriers are limited human resources and capacity variations across schools. This research highlights that collaborative governance is a crucial element in the successful development of locally-based educational innovations.